2022
DOI: 10.1016/j.lanwpc.2021.100350
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Defined by 2017 ACC/AHA Guideline, Ideal Cardiovascular Health Metrics, and Risk of Cardiovascular Disease: A Nationwide Prospective Cohort Study

Abstract: Summary Background The updated definition of hypertension by the American College of Cardiology (ACC) and the American Heart Association (AHA) is an important paradigm shift and has lead to extensive discussion. We aimed to examine the association between the updated blood pressure (BP) categories and the risk of cardiovascular diseases (CVDs) with potential modifications from other cardiovascular health metrics (CVHMs). Methods This prospective study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Moreover, participants with stage 1 hypertension having ≥4 ideal CVH components did not have significantly greater CVD risk compared with all participants without hypertension (HR, 1.04 [95% CI, 0.83–1.31]). 23…”
Section: Cardiovascular Healthmentioning
confidence: 99%
“…Moreover, participants with stage 1 hypertension having ≥4 ideal CVH components did not have significantly greater CVD risk compared with all participants without hypertension (HR, 1.04 [95% CI, 0.83–1.31]). 23…”
Section: Cardiovascular Healthmentioning
confidence: 99%
“…A nationwide prospective cohort study conducted across mainland China reported that hypertensive patients with more ideal cardiovascular health metrics have significantly reduced incidents of CVD. 15 In another prospective study with the participation of 5488 hypertensive patients, Ying et al 28 found that an increased number of ideal cardiovascular health metrics was inversely related to the risk of ischemic stroke in participants with hypertension. However, only the baseline cardiovascular health metrics was regarded as exposure of interest and the subsequent changes in cardiovascular status were ignored in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Plenty of evidence has proved that higher CHS was associated with a lower risk of MI in both the general population and hypertensive patients. [13][14][15] However, the past studies only stressed the association between single CHS and MI risk while the longitudinal association between changes in CHS over time and MI risk in hypertensive patients was not examined.…”
mentioning
confidence: 99%
“…In addition, hypertensive patients have multiple risk factors ( 27 , 40 ), and multiple cardiovascular disease risk factors will proportionately increase the risk of coronary artery, cerebrovascular, and renal disease ( 27 , 29 ). An important part of BPHS is to assist with interventions of modifiable risk factors for hypertensive patients, including salt reduction, regular physical activity, weight reduction, smoking cessation, alcohol restriction, and reduction of psychological stress, consistent with the global practice guidelines developed by ISH ( 27 ), American College of Cardiology ( 41 ) and with the support of extensive research evidence done on hypertension ( 8 , 42 46 ). We also found hypertensive patients in the BPHS group had lower rates of smoking and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling blood pressure to a normal state reduces the risk of cardiovascular events and all-cause mortality (6)(7)(8). The trend of cardiovascular disease will be directly impacted by how hypertension is managed in primary medical and health organizations (community health centers, township health centers, and village clinics) (9).…”
Section: Introductionmentioning
confidence: 99%